Disentangling the Effects of SFON (Spontaneous Focusing on Numerosity) and Symbolic Number Skills on the Mathematical Achievement of First Graders. A Longitudinal Study - Gloor, Noemi; Leuenberger, Delia; Moser Opitz, Elisabeth (Frontiers in Education, 2021)
Research has established that Spontaneous Focusing on Numerosity (SFON) and symbolic number skills (e.g., counting out loud, counting objects, linking small magnitudes and numbers) are predictors of mathematical achievement in primary school. However, little is known about the relationship between SFON and symbolic number skills, or whether one of these factors is more influential on a child’s subsequent mathematical achievement. This study investigated the effect of SFON and symbolic number skills on mathematical achievement at the end of Grade 1 by controlling for first language, gender, working memory and nonverbal IQ. Participants were N = 1,279 first graders. SFON, symbolic number skills and control variables (first language, gender, working memory, and nonverbal IQ) were measured at the beginning of Grade 1. SFON was assessed with a verbally-based task. Data on mathematical achievement was collected at the end of Grade 1. Descriptive statistics demonstrated that the children’s SFON was relatively low at the beginning of Grade 1. Structural equation modeling was used to examine the relationship between SFON, symbolic number skills and mathematical achievement at the end of Grade 1. The results revealed a weakly significant correlation between SFON and symbolic number skills. SFON and symbolic number skills were significant predictors of mathematical achievement at the end of Grade 1. However, the effect of symbolic number skills on mathematical achievement was greater than the effect of SFON. It is therefore concluded that numerical skills are more important than SFON for predicting mathematical achievement over the course of first grade.